The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/8078646
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Promote Larynx Squamous Cell Carcinoma Progression via Activating the IL-17/JAK/STAT3 Pathway

Abstract: Laryngeal squamous cell carcinoma (LSCC) is the main type of laryngeal cancer with poor prognosis. Incidence of LSCC increases every year, posing a great threat to human health. The underlying mechanism needs further study. Neutrophils are the most prevalent type of immune cells, which play vital roles in crosstalk between the microenvironment and cancer cells. In our study, we aim to figure out the complex regulation between neutrophils and LSCC. Our experiments showed that LSCC cells could promote the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…STAT3 has been found to undergo phosphorylation by several pro-inflammatory cytokines, including IL-17 [51]. Accumulating evidence indicates that activation of the IL-17/JAK/STAT3 pathway plays a significant role in tumor metastasis and growth [52]. Numerous studies have demonstrated that suppression of the JAK/STAT3 pathway by inhibitors can inhibit cancer cell invasion and promote apoptosis [44,53].…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 has been found to undergo phosphorylation by several pro-inflammatory cytokines, including IL-17 [51]. Accumulating evidence indicates that activation of the IL-17/JAK/STAT3 pathway plays a significant role in tumor metastasis and growth [52]. Numerous studies have demonstrated that suppression of the JAK/STAT3 pathway by inhibitors can inhibit cancer cell invasion and promote apoptosis [44,53].…”
Section: Discussionmentioning
confidence: 99%
“…Keratinization is also associated with tumor metastasis, with transformed keratinocytes invading the dermis through the BM leading to aggressive cutaneous squamous cell carcinomas with substantial metastatic potential ( 41 ). IL-17 signaling pathway is also a classic cancer-related signaling pathway, which has been extensively studied in breast cancer, colorectal cancer, and squamous cell carcinoma ( 42 44 ).…”
Section: Discussionmentioning
confidence: 99%
“… 56 Numerous studies have reported that IL-17 levels are elevated in HNSCC and that targeting IL-17 production can impede tumor cell proliferation. 57 , 58 IL-17 promotes tumor cell proliferation by activating the JAK/STAT3 pathway 59 and inhibits apoptosis by blocking FAS-associated death domain protein through the PI3K/AKT pathway. Consistent with this, silencing IL-17 expression in laryngeal cancer cells triggered apoptosis through the PI3K/AKT/FAS/FASL pathway.…”
Section: Role Of Inflammation-related Mediators In the Progression Of...mentioning
confidence: 99%